Unexpected pincer-type coordination (κ3-SBS) within a zerovalent platinum metallaboratrane complex - Owen, Gareth R.; Gould, P. Hugh; Hamilton, Alex; Tsoureas, Nikolaos (Dalton Transactions, 2010)
The first structurally characterised zerovalent platinum complex to contain a tridentate pincer-type coordination mode (κ3-SBS) is presented, raising further questions concerning the geometries and trans influence of Z-type ligands. © The Royal Society of Chemistry 2010.